2013
DOI: 10.1080/09669582.2012.750328
|View full text |Cite
|
Sign up to set email alerts
|

Testing a model of effective interpretation to boost the heritage tourism experience: a case study in Macao

Abstract: While the impact of tour guides' interpretation on tourism experience is well acknowledged, little research has been conducted on the production of effective interpretation by tour guides. In this study, effective interpretation is defined as producing a positive outcome on tourists' knowledge and understanding of the visited heritage site, feelings and emotion, satisfaction and likelihood of visiting other relevant nearby heritage sites. Based on a literature review, a conceptual model of effective interpreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 47 publications
0
33
2
Order By: Relevance
“…The highest correlation was for the PM media and the lowest was for the TG. This finding was not supported by previous studies; earlier studies reporting that TG can contribute toward induced states of mindfulness better than other mediums, such as PM (Cohen, 1985;Io, 2013;Reisinger & Steiner, 2006). However, the respondents in the current study did not report a more significant effect for TG on inducing mindfulness compared with PM or EDA mediums.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The highest correlation was for the PM media and the lowest was for the TG. This finding was not supported by previous studies; earlier studies reporting that TG can contribute toward induced states of mindfulness better than other mediums, such as PM (Cohen, 1985;Io, 2013;Reisinger & Steiner, 2006). However, the respondents in the current study did not report a more significant effect for TG on inducing mindfulness compared with PM or EDA mediums.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, from the perspective of visitors, the personal connection feature of the PM medium, and the interactivity/participation feature of the TG medium can contribute toward greater mindfulness more so than other features. Previous studies have suggested the use of TG because of the potential for tour guides to interact with visitors more effectively (Io, 2013;Reisinger & Steiner, 2006). However, the visitors surveyed in this study indicated that the PM medium was more successful in establishing a personal connection between them and the site than TG medium and in inducing mindfulness.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Interpretation refers to modes of visitor communication such as signs, exhibits, brochures, talks and costumed performances that are specifically designed to help visitors understand, appreciate and engage with heritage sites. Studies in a wide range of settings indicate that well-designed interpretation has the potential to enhance the visitor experience (Van Dijk & Weiler, 2009), encourage visitors to care about the site and its resources (Huang & Weiler, 2010), minimise the negative impacts of tourism (Moscardo, 1998;Weiler & Kim, 2011), prompt visitors to donate time or money to conservation initiatives (Powell & Ham, 2008), change visitors' knowledge, attitudes and facilitate the adoption of environmentally sustainable behaviour (Ballantyne, Packer, & Falk, 2011;Munro, Morrison-Saunders, & Hughes, 2008) and enhance the economic viability of the site and thus help pay for conservation measures (Io, 2013;Wong, 2013). Because interpretation contributes to visitors' understanding of the cultural, environmental and social significance of heritage sites, researchers also claim it plays a pivotal role in creating both demand and support for the conservation of historic places (Huang & Weiler, 2010;Io, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Man-U Io (2013) created an interpretation model which held that interpreter's knowledge, service attitude, communicative competence and emotion quotient affect visitors' travel experience positively. Besides, the model has been verified in empirical studies which emphasized that training class for tour guides should attach importance to affective management of visitors since this is the key factor to enhance visitors' emotional involvement and experience [11] . Marc Stern and Robert Powell (2014) studied 376 interpretive programs in national parks in the U.S. and found effective personal interpretation involved confidence, true feeling involvement and personal charm demonstration, timely response to visitors' questions and requests et al and should avoid taking knowledge gain as the goal of interpretation.…”
Section: A Studies Concerning Characteristics Of Effectivementioning
confidence: 98%